CFD modeling of the turbulent dispersion of liquid droplets in a vessel using a correlation based on local droplet size distribution. Issue 11 (2nd November 2022) - Chen, Luming; Li, Yibin; Chen, Bingbing; Wang, Pengfei; Zheng, Sanlong; Zhang, Wei
Abstract: Macro-mixing of two immiscible liquid in a stirred tank is strongly influenced by the turbulence generated due to the rotating impeller, consequently affecting the dispersion of the formed liquid droplets. The present study conducted a CFD numerical analysis on the liquid-liquid mixing in a stirred tank that has adopted the Rushton turbine impeller based on the Eulerian-Eulerian approach, coupled with a local turbulence and empirical equations-based dispersed phase droplet size correlation. The simulation results have clearly demonstrated that the proposed local droplet size distribution correlation can well model the distribution of dispersed phase drops in the stirred tank comparing with the experimental data and the results published in the open literature. In particular, it has been found that CFD modeling coupled with the proposed size distribution correlation can reasonably predict dispersed phase volume fraction above the impeller region and the salient characteristics of liquid-liquid macro-mixing in the tank. The likely mechanism that controls the droplet size distribution was also discussed.